SEBARAN, PROBABILITAS DAN FAKTOR-FAKTOR YANG MEMPENGARUHI PROBABILITAS TERJADINYA KEMISKINAN PETANI SAYURAN DI KECAMATAN SINDANG DATARAN KABUPATEN REJANG LEBONG - Wiyanto, Hadi; Sukiyono, Ketut; Priyono, Basuki Sigit (Jurnal AGRISEP, 2014)
This study aims to determine the poverty level of horticultural farmers based on the Sayogyo poverty line, its distribution and the factors that influence the probability of poverty occurrence in the village Talang Belitar Sindang Dataran sub district Rejang Lebong district. Data were analysed using a logit model with 55 respondents of horticultural farmers. The results showed that 60 percent of farmers can be considered as poor. This number is distributed to the poorest as much as 75.76 percent, while the mediocre poorers were 6.06 percent and the poorer were 18.18 % are poor. Logit model estimation results that land area and number of dependences have a real effect on the probability of farmers being poor while education, access to financial institutions and the existence of alternative business do not.